(untitled) (World Science, 2016)
Grow requirements for precision measurements of various physical quantities, including microelectromechanical measurement devices, leading to the need to introduce in the applied processes allow additional operations lead product output parameters to values corresponding to a precision instrument traditional performance. The paper deals with the use of ion implantation, as the development of the electronics industry manufacturing operation, for modifying the elastic moduli and dependent elasticity coefficients of the mechanical part of the MEMS. It is shown that the range of possible changes in these ratios as high as 12%, which allows us to consider this method as a base for MEMS adjustments.